Ответы и объяснения

2013-08-11T23:48:05+04:00
\frac{sin(\pi+\alpha)*sin(2\pi+\alpha)}{tg(\pi-\alpha)*cos(\frac{3\pi}{2}+\alpha)}=\frac{-sin\alpha*sin\alpha}{-tg\alpha*cos\alpha}=\frac{-sin\alpha*sin\alpha}{-\frac{sin\alpha}{cos\alpha}*cos\alpha}=\frac{-sin\alpha*sin\alpha}{-sin\alpha}=sin\alpha
Использованы формулы приведения. 

Если остались вопросы пишите в личку.
Лучший Ответ!
  • AlbuRin
  • светило науки
2013-08-12T07:22:52+04:00
Sin(pi  +  a)*sin(2pi  +  a) / (tg(pi  -  a) * cos(3pi/2  +  a))  =  -sina * sina / (-tga * sina)  =
=  sin^2a / ( (sina/cosa) * sina)  =  sin^2a / (sin^2a/cosa)  =  sin^2a * (cosa/sin^2a)  =
=    cosa
Ответ.      cosa.